Basin Scale Variation on the Composition and Diversity of Archaea in the Pacific Ocean - Xia, Xiaomin; Guo, Wang; Liu, Hongbin (Frontiers in Microbiology, 2017)
The Archaea are a widely distributed group of prokaryotes that inhabit and thrive in many different environments. In the sea, they play key roles in various global biogeochemical processes. Here, in order to investigate the vertical profiles of archaeal community across a large geographic distance, the compositions of archaeal communities in seven seawater columns in the Pacific Ocean were investigated using high throughput 454 pyrosequencing of the 16S rRNA gene. The surface archaeal communities showed lower diversity and greater variability than those in the deeper layers. Two of the major archaeal phyla that displayed different depth preferences were Thaumarchaeota and Euryarchaeota. The majority of Thaumarchaeota belonged to Marine Group I (MGI), which had high relative abundance in deep water. In contrast, Euryarchaeota, which mainly consisted of Marine Group II (MGII) and III (MGIII), were dominant in the surface layer. Compared with MGI and MGII, MGIII were less abundant in seawater and generally absent from the surface water of the subarctic Pacific. In addition, niche separation in the MGI, MGII and MGIII subgroups was also observed. For example, MGI.C and MGII.A (the major subgroups of MGI and MGII, respectively) displayed a strong negative correlation with each other. The highest level of archaeal diversity was found in the core of an oxygen minimum zone (OMZ) located off Costa Rica, which resulted from the co-occurrence of both anaerobic and aerobic archaea. For example, methanotrophic archaea ANME-2, methanogenic archaea and several sediment origin archaea, such as Marine Benthic Group A (MBGA) and Bathyarchaeota, were all detected at relatively high abundance in the OMZ. Together, our findings indicate that vertical heterogeneities along water columns and latitudinal differentiation in the surface waters are ubiquitous features of archaeal communities in the Pacific Ocean, and the OMZ off Costa Rica is an archaeal biodiversity hot-spot.